2016
DOI: 10.1016/j.yjmcc.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast–myocyte coupling in the heart: Potential relevance for therapeutic interventions

Abstract: Cardiac myocyte-fibroblast electrotonic coupling is a well-established fact in vitro. Indirect evidence of its presence in vivo exists, but few functional studies have been published. This review describes the current knowledge of fibroblast-myocyte electrical signalling in the heart. Further research is needed to understand the frequency and extent of heterocellular interactions in vivo in order to gain a better understanding of their relevance in healthy and diseased myocardium. It is hoped that associated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 143 publications
(164 reference statements)
2
74
0
Order By: Relevance
“…Cx43-containing gap junctions electrically couple cardiomyocytes, enable electrical impulse propagation and consequently coordinate synchronous heart muscle contractions (Shibata and Yamamoto, 1977). In addition, Cx43-containing gap junctions couple cardiomyocytes with non-cardiomyocytes, which can then alter the electrophysiological properties of cardiomyocytes (Ongstad and Kohl, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Cx43-containing gap junctions electrically couple cardiomyocytes, enable electrical impulse propagation and consequently coordinate synchronous heart muscle contractions (Shibata and Yamamoto, 1977). In addition, Cx43-containing gap junctions couple cardiomyocytes with non-cardiomyocytes, which can then alter the electrophysiological properties of cardiomyocytes (Ongstad and Kohl, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…104 Key foci of current translational research in this context are on regenerating heart muscle lost to disease by reprogramming fibroblasts to trans-differentiate into cardiomyocytes, and on reducing fibrosis or the extent of pathologic scarring that occurs in response to injury and/or disease (Box 1)…”
Section: Fibroblasts and Adult Myocardial Homeostasismentioning
confidence: 99%
“…Recent studies, however, identified endothelial cells as the predominant cell type in both mouse and human adult ventricles, representing 45–55% of the total cell count (compared with ~30% cardiomyocytes and ~15% fibroblasts), although, similar to skeletal muscle, taking up only a small fraction of the ventricular volume [28]. While evidence for electrical coupling between fibroblasts and cardiomyocytes is present in vitro [29, 30], the ability of these cell types to form functional heterocellular gap junctions in vivo is still widely debated [31, 32]. Both in skeletal and cardiac muscles, blood is delivered to cells in a hierarchical manner with primary arteries progressively bunching into smaller vessels and capillaries [33, 34].…”
Section: Striated Muscle Structure and Functionmentioning
confidence: 99%